Understanding Boko Haram: terrorism and insurgency in Africa - Hentz, James J.; Solomon, Hussein (Contemporary terrorism studies, 2017)
Introduction: theorizing Boko Haram : understanding the terrorist threat / Hussein Solomon -- The long durée -- Boko Haram : a jihadist enigma in Nigeria / Marc-Antoine Pérouse de Montclos -- The Boko Haram paradox : ethnicity, religion, and historical memory in pursuit of a caliphate / Zacharias P. Pieri and Jacob Zenn -- Old wine in a new bottle : ideological and operational linkages between maitatsine and Boko Haram revolts in Nigeria / Iro Aghedo -- The nigerian state and Boko Haram -- Boko Haram and the widening of cleavages in Nigeria / Azeez Olaniyan and Lucky Asuelime -- Identity, deprivation, terror : why Boko Haram rebels / Daniel Agbiboa -- The elusive quest for peace : Boko Haram and the hollowness of Nigeria's counterinsurgency strategy and weak security architecture / Olabanji Akinola -- Mopping the wet floor of a leaking roof : fighting terror while overlooking radicalization / Ibaba Samuel Ibaba and Anthony Okoye -- Responses -- Portents of a fractured Boko Haram for Nigeria's counter-terrorism strategy and tactics / Gbemisola Abdul-Jelil Animasawun -- Effective counter-terrorism against Boko Haram : empirical assessments of coercion, delegitimization, incentivization and denial strategies in Nigeria (2009-2014) / John A. Stevenson, Amy Pate, Elvis Asiamah -- The Western response / Virginia Comolli -- Responding to Boko Haram : interrogating the effectiveness of state and regional intervention approaches / Kwesi Aning, Mustapha Abdallah and Festus Aubyn -- Conclusion: Nigeria and a war across states in Northwest Africa / James J. Hentz